PENGARUH VARIASI FLUKS TERHADAP SIFAT FISIK DAN MEKANIK HASIL SAMBUNGAN LAS GMAW (GAS METAL ARC WELDING) BAJA AISI 1018 - Purwaningrum,, Yustiasih; Firmansyah, Daffa Rizal; Noorseta, Edo Setya (Program Studi Teknik Mesin Universitas Tarumanagara, 2023)
The aimed of this study was to determine the effect of flux variations on physical and mechanical properties of GMAW welded joints. This research uses AISI 1018 steel with a size of 300 mm x 100 mm and a thickness of 5 mm. The welding process is carried out using the Gas Metal Arc Welding (GMAW) method, ER70S-6 filler and shielding gas mixture of Argon and CO2 (50% and 50%). The flux variations used are ZnO, Al2O3, dan SiO2.. The tests carried out are dye penetrant testing, chemical composition testing, microstructure observation, tensile testing, bending testing and hardness testing. The results of dye penetrant testing show that welding results with all flux variations can be well jointed. Testing the chemical composition of the welding results shows that the chemical elements of the welding results will rise according to the main chemical elements of the flux. . The highest value of tensile strength and bending strength of welds is found in welds with the addition of ZnO flux. . This is in accordance with the results of microstructure observations that show welds with ZnO flux have the most microstructures in the form of accicular ferrite compared to grain boundary ferrite and widmanstatten ferrite. Accicular microstructure will increase the strength and toughness of the material due to its small shape and random directional orientation. The hardness number of welding results for all welding variations has almost the same value, which is approximately 190 VHN.